2009
DOI: 10.1155/2009/695837
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Ganglion Structures in Esophageal Atresia: A Morphologic and Immunohistochemical Study

Abstract: Introduction and Aim. Disorders of esophageal motility causing dysphagia and gastroesophageal reflux are frequent in survivors to esophageal atresia (EA) and distal tracheoesophageal fistula (TEF). The aim of the present study was to investigate the histologic and immunohistochemical features in both esophageal atretic segments to further understand the nature of the motor disorders observed in these patients. Material and Methods. Esophageal specimens from 12 newborns with EA/TEF and 5 newborns dead of unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…Evaluation of anti-NF expression revealed a more dense, intrinsically fibrous esophageal fibrillation network in cases of esophageal atresia with inferior tracheoesophageal fistula, data similar to other studies [21]. At the same time some studies have described a diminished or even negative expression of this suggestive marker for diffuse neural diffusion [4,30].…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Evaluation of anti-NF expression revealed a more dense, intrinsically fibrous esophageal fibrillation network in cases of esophageal atresia with inferior tracheoesophageal fistula, data similar to other studies [21]. At the same time some studies have described a diminished or even negative expression of this suggestive marker for diffuse neural diffusion [4,30].…”
Section: Resultssupporting
confidence: 83%
“…Several immunohistochemical studies have found poor or negative immunoreactivity expression of neuronal markers, including neuron-specific enolase [16]. The anti-NSE 0 or 1+ expression found in some proximal areas of both atresied segments is characteristic of a neoglicogenesis deficiency [30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations